The Construction of the View on Journalism: Perceções dos estudantes do ensino superior em Portugal - Lopes, Anabela; Silvestre, Cláudia; Mata, María José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The perspective of future journalists on the profession is important for a critical assessment of the way the academy, in its communication/journalism courses, prepares them. The results of a questionnaire survey to undergraduate and master's students of communication/journalism, from 11 Portuguese higher education institutions, point to a mismatch between perceptions about current journalism and future ex- pectations, which led us to reflect on the role of educational institutions, which ap- pear more as promoters of critical view of journalism, than promoters of proactive attitudes in the search for answers to the various challenges identified by students.